2015
DOI: 10.1002/lsm.22426
|View full text |Cite
|
Sign up to set email alerts
|

Ablative fractional laser resurfacing with topical paromomycin as adjunctive treatment for a recalcitrant cutaneous leishmaniasis wound

Abstract: AFR with laser-assisted delivery of topical paromomycin represents a novel treatment option for resistant, non-healing CL wounds. The technique may prove additionally useful for concurrent mitigation of scarring related to CL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In addition, the channels that the ablative fractional CO 2 laser creates allow for deeper penetration and greater bioavailability of topically applied medications . The use of laser‐assisted drug delivery for leishmaniasis was published in one case report treating a recalcitrant leishmania lesion with fractional ablative CO 2 laser followed by topical paromomycin with good clinical and aesthetic outcomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the channels that the ablative fractional CO 2 laser creates allow for deeper penetration and greater bioavailability of topically applied medications . The use of laser‐assisted drug delivery for leishmaniasis was published in one case report treating a recalcitrant leishmania lesion with fractional ablative CO 2 laser followed by topical paromomycin with good clinical and aesthetic outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the successful use of a fractional ablative laser in assisted topical drug delivery, achieving results similar to those of intralesional injections . The use of laser‐assisted drug delivery for leishmaniasis was reported on in a case report of the treatment of a recalcitrant leishmania lesion using a fractional ablative carbon dioxide (CO 2 ) laser followed by topical paromomycin with good clinical and aesthetic outcome, but the use of lasers as an alternative for intralesional injection of pentavalent antimony for CL has not been previously described.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events were reported in six patients from two case reports. Basnett et al 30 reported the use of ablative fractional laser resurfacing for a 16-year-old female with several nonhealing lesions of cutaneous leishmaniasis on the bilateral and upper extremities. After two treatments, the patient's wounds healed completely without evidence of infection and with minimal scarring.…”
Section: Case Reportsmentioning
confidence: 99%
“…Fractional ablative CO 2 laser is an effective treatment for cutaneous atrophic scars resulting from CL (14). Furthermore, the use of laser-assisted drug delivery for leishmaniasis was published in one case report treating recalcitrant active Leishmania lesion with fractional ablative CO 2 laser followed by topical paromomycin with good clinical and aesthetic outcome (15).…”
Section: Fractional Ablative Co 2 Laser Followed By Topical Applicatimentioning
confidence: 99%